(untitled) - Bentley, Duncan (Alphen aan den Rijn,Frederick, MD, 2007)
The theory and framework of taxpayers’ rights to provide support and reassurance for particular approaches to tax administration design; the updated principles for analysis of any tax system; the classification of taxpayers’ rights so that they can understand why much tax administration and procedure operates in the way it does; the design of legislative mechanisms to assist in the design and drafting of tax administration; the design and implementation of dispute resolution systems in tax administration; specific detail on the powers and duties of tax administrators and how they should be exercised; the design and implementation of taxpayers’ charters and other guidelines on taxpayers’ rights; specific detail on the rules and procedures in tax administration, relating in any way to taxpayers’ rights, and how they should be applied; and a clear and articulated standard of best practice in tax administration and governance for quality assurance purposes.
Keywords: Tax administration and procedure,Taxpayer compliance,Thực hiện nộp thuế thu nhập,Thủ tục quản lý thuế